Dynamic speckle analysis with smoothed intensity-based activity maps. (June 2017) - Stoykova, Elena; Berberova, Natalia; Kim, Youngmin; Nazarova, Dimana; Ivanov, Branimir; Gotchev, Atanas; Hong, Jisoo; Kang, Hoonjong
Abstract: Pointwise intensity-based algorithms are the most popular algorithms in dynamic laser speckle measurement of physical or biological activity. The output of this measurement is a two-dimensional map which qualitatively separates regions of higher or lower activity. In the paper, we have proposed filtering of activity maps to enhance visualization and to enable quantitative determination of activity time scales. As a first step, we have proved that the severe spatial fluctuations within the map resemble a signal-dependent noise. As a second step, we have illustrated implementation of the proposed idea by applying filters to non-normalized and normalized activity estimates derived from synthetic and experimental data. Statistical behavior of the estimates has been analyzed to choose the filter parameters, and substantial narrowing of the probability density functions of the estimates has been achieved after the filtering. The filtered maps exhibit an improved contrast and allowed for quantitative description of activity. Highlights: Intensity-based dynamic speckle analysis allows for building pointwise estimates. Fluctuations of the estimates are signal-dependent and worsen activity map contrast. Filtering the map for better contrast and visualization enhancement is proposed. Quantitative temporal evaluation of activity is possible from a set of smoothed maps. Experimental verification is obtained with three estimates of a structure function.